Getting the diagnosis right: approaches to new diagnostics for childhood tuberculosis - Olbrich, L (2022)
Tuberculosis (TB) remains a major cause for morbidity and mortality in children, and the very young and immunocompromised are especially at high risk. A major hurdle is a timely diagnosis, as microbiological confirmation – regarded as the reference standard – remains uncommon and the available tools are neither child-friendly, user-friendly, nor sufficiently accurate.